Interleukin-17 levels in gingival crevicular fluid of aggressive periodontitis and chronic periodontitis patients - Anand Narayanrao Wankhede; Prasad Vijayrao Dhadse (Wolters Kluwer Medknow Publications, 2022)
Context: Interleukin-17 (IL-17) plays an important function in initiation, progression of any inflammatory condition. It is a pro-inflammatory cytokine and considered to be founding member. Periodontitis being an inflammatory condition of periodontium, IL-17 does have a potential role in periodontitis. The current research has shown positive correlation between the IL-17 and severity of periodontitis. Therefore, this research study aimed to evaluate the levels of IL-17 in aggressive periodontitis (AgP), chronic periodontitis (CP), and "healthy gingival sites." Materials and Methods: A total of 45 selected subjects (90 samples) were equally divided into three different groups. Group 1 (Healthy gingiva on clinical examination): Subjects with healthy gingiva and no evidence of periodontal attachment level (PAL), probing pocket depth (PPD) <3 mm papillary bleeding index (PBI) <1. Group 2 (AgP): Subjects having age <35 years with at least six permanent teeth apart from the incisors and first molars with PPD and PAL ≥5 mm. Group 3 (CP): It consist of subjects with clinical features of inflammation of gingiva with minimum six teeth in each jaw, with PPD ≥4 mm, PAL ≥4 mm. IL-17 levels were analyzed by using Gingival crevicular fluid (GCF). It was collected from the sulcus of first maxillary molar sites for quantitative analysis. Results: GCF IL-17 levels in AgP were found to be 1.12 ± 0.29, 1.96 ± 1.71 in CP and 0.64 ± 0.23 in healthy gingival sites. Clinical parameters such as (1) plaque index (Turesky et al., modification of Quigley-Hein), (2) PPD, (3) PBI were higher (significantly) in periodontitis group as compared to healthy gingiva. Positive correlation was found to be significant between levels of IL-17 with PAL and PPD in AgP however in cases of CP, positive correlation of IL-17 levels was found only with PAL but not PPD. Conclusion: Our study shows that the IL-17 levels were comparatively higher in GCF of AgP, CP in comparison to healthy gingiva, but the GCF IL-17 levels were higher in CP as compared to AgP.